2017
DOI: 10.22159/ajpcr.2017.v10i10.18879
|View full text |Cite
|
Sign up to set email alerts
|

COW URINE DISTILLATE AS A BIOENHANCER FOR ANTIMICROBIAL & ANTIPROLIFERATIVE ACTIVITY AND REDISTILLED COW URINE DISTILLATE AS AN ANTICLASTOGEN AGENT

Abstract: Objective: The objective of this study was to prove that cow urine distillate (CUD) is a bioenhancer for antimicrobial activity and antiproliferative activity, redistilled CUD (RCUD) as an anticlastogen agent. Methods:The antimicrobial activity of rifampicin with CUD at different concentrations was determined against pathogenic Escherichia coli by well puncture method. The Penicillin and ciprofloxacin in combination with CUD at different/increasing concentrations against pathogenic E. coli culture were also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…We selected four different bacterial species, which are the common cause of human infections in this part of the country. Distilled cow's urine was initially tested for sterility and was found to be sterile as observed in the earlier studies (16,17). Sterile CUD was tested on the standard strain of E. coli ATCC 25922, P. aeruginosa ATCC 27853, S. aureus ATCC 25923, E. faecalis ATCC 29212, to know the MIC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected four different bacterial species, which are the common cause of human infections in this part of the country. Distilled cow's urine was initially tested for sterility and was found to be sterile as observed in the earlier studies (16,17). Sterile CUD was tested on the standard strain of E. coli ATCC 25922, P. aeruginosa ATCC 27853, S. aureus ATCC 25923, E. faecalis ATCC 29212, to know the MIC.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal value of cow's urine was appreciated long ago as its efficacy and mechanism of antibacterial effect remain elusive, thorough scientific validation is required to prove its efficacy. Few studies from different Indian states like Madhya Pradesh, Kerala, Karnataka, Gujarat, and New Delhi, have reported the antibacterial effect of cow's urine (12)(13)(14)(15)(16)(17). Interestingly, urine of most of the native cow exhibit antimicrobial properties but not the urine of buffalo, goat and crossbred cows (18).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the presence of many essential micronutrients (calcium, phosphorous), vitamins (B1, B2, and C), and enzymes (amylase, acid phosphatase, lactate, and lactate dehydrogenase, etc.) in cow urine (Mohanvel et al 2017 ; Ketan et al 2020 ). Studies also confirmed that cow dung harbors a rich microbial diversity and a good source of essential enzymes and metabolites of human interest (Gupta et al 2016 ; Semwal et al 2019).…”
Section: Cow Products For Human Health Managementmentioning
confidence: 99%
“…Lactoferrin is a major iron-binding glycoprotein from cow milk known to have an immunomodulatory role, and recently, their immunocompetence efficacy has been emphasized against SARS coronavirus 2 (SARS-CoV-2) or COVID-19 (Mann and Ndung 2020). The active constituents of cow urine prevent the free radical formation, act as bio-enhancer, reduce blood glucose, and efficiently repair the damaged DNA, thus showing anticancer and anti-diabetic efficacy (Dutta et al 2006 ; Mohanvel et al 2017 ). Recently, Padvi et al ( 2020 ) suggested that cow urine mediated synthesized copper oxide nanoparticles (CuO NPs) can be used for antineoplastic therapy.…”
Section: Cow Products For Human Health Managementmentioning
confidence: 99%
See 1 more Smart Citation